2017
DOI: 10.1186/s12943-017-0743-3
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 regulates autophagy associated chemoresistance via miR-23b-3p sequestration in gastric cancer

Abstract: BackgroundChemoresistance has long been recognized as a major obstacle in cancer therapy. Clarifying the underlying mechanism of chemoresistance would result in novel strategies to improve patient’s response to chemotherapeutics.MethodslncRNA expression levels in gastric cancer (GC) cells was detected by quantitative real-time PCR (qPCR). MALAT1 shRNAs and overexpression vector were transfected into GC cells to down-regulate or up-regulate MALAT1 expression. In vitro and in vivo assays were performed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
230
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(248 citation statements)
references
References 38 publications
6
230
0
Order By: Relevance
“…Liu et al showed the tumor‐promoting role of HOTAIR in gastric cancer progression through positively regulating HER2 expression by sponging miR‐331‐3p. In addition, expression of several miRNAs, including miR‐675, miR‐145‐5p, miR‐152, miR‐145, miR‐23b‐3p, and miR‐335‐5p, are significantly dysregulated by lncRNAs and then change the expression of target mRNAs in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed the tumor‐promoting role of HOTAIR in gastric cancer progression through positively regulating HER2 expression by sponging miR‐331‐3p. In addition, expression of several miRNAs, including miR‐675, miR‐145‐5p, miR‐152, miR‐145, miR‐23b‐3p, and miR‐335‐5p, are significantly dysregulated by lncRNAs and then change the expression of target mRNAs in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported that lncRNAs are involved in multiple malignant tumors including OS . Metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) is located at chromosome 11q13.1 and is discovered as a new cancer‐associated lncRNAs in various cancers . Wang Y found that MALAT1 promoted OS cell metastasis and proliferation via serving as a ceRNA of ROCK1 and ROCK2 .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Metastasisassociated lung adenocarcinoma transcript 1 (MALAT1) is located at chromosome 11q13.1 and is discovered as a new cancer-associated lncRNAs in various cancers. [23][24][25][26] Wang Y found that MALAT1 promoted OS cell metastasis and proliferation via serving as a ceRNA of ROCK1 and ROCK2. 21 Luo W illustrated that MALAT1 contributed to an increased expression of transforming growth factor alpha (TGFA) and facilitated OS cell growth through an inhibition of miR-376a.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, lncRNA expression is relatively tissue‐specific, and studies have shown that one lncRNA may play different roles by targeting different pathways in different cell types. For example, the lncRNA MALAT1 plays different roles by regulating different miRNAs and pathways in GC, colon cancer, and retinoblastoma …”
Section: Discussionmentioning
confidence: 99%
“…For example, the lncRNA MALAT1 plays different roles by regulating different miRNAs and pathways in GC, colon cancer, and retinoblastoma. [45][46][47] A comprehensive database that provides the functions of lncRNAs and their target genes is still lacking. Therefore, it is essential to use online software and databases to predict lncRNA interactions, cooperation, localization, and function.…”
Section: Target Genes Of the Ebv-related Lncrnasmentioning
confidence: 99%